Sustainable environmental manufacturing practice (SEMP) and firm performance: Moderating role of environmental regulation - Adebambo, Hameed O.; Ashari, Hasbullah; Nordin, Norani (Canadian Center of Science and Education, 2014)
Theoretical evidence shows that a considerable amount of attention has been given to environmental issues in academic researches in the past years and the link between sustainable environmental practices and firm performance remains inconclusive.One of the reasons for this inconsistent relationship is due to the increasing regulatory requirements of the environmental sustainable practices which have become increasingly stringent on yearly basis.This study investigates the moderating effect of environmental regulation on the relationship between sustainable environmental manufacturing practices and firm performance. Data was collected by using a mail survey questionnaire from the manufacturing companies in Malaysia and analyzed with PLS-SEM.The result of the empirical investigation found that environmental regulation only moderates the relationship between SEMP and environmental performance.The relationships between SEMP; and financial and operational performance were not significantly moderated by stringent environmental regulation.The study recommends that environmental policy makers should revisit the blueprint about environmental regulation on environmental practices to provide supportive environmental policies that will enhance a better financial and operational performance in manufacturing industry.